Về các quan hệ tối giản ở dạng không chuẩn một - Sơn, Trần Thái (Journal of Computer Science and Cybernetics, 2016)
In this paper the propreties of the nest and unnest operations of Non-First normal form Relations (NFR) are discussed. Some necessary and sufficient conditions, under which a collection of irreducible relations and a collection of canonical relations over a set of attributes E = {E1, E2} are identified, are proposed.